FREQUENCY OF DIFFERENT VALVULAR LESIONS OF RHEUMATIC HEART DISEASE PRESENTING TO A TERTIARY CARE HOSPITAL - Rehman, Javaid ur; Marwat, Zahid Irfan; Ahmad, Zahoor; Shah, Islam; Khattak, Asifullah; Falah, Sheikh Fahad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Rheumatic Hearth Disease (RHD) is still prevalent in our country and a great source of morbidity. This study was done with an objective to determine relative frequency of different valvular lesions of RHD presenting in a tertiary care hospital. Methods: This cross sectional study was conducted at the Cardiology Department of Hayatabad Medical Complex, Peshawar. A total of 171 cases of RHD were included through consecutive sampling technique. Results: There were 64.33% females. Mean age was 25.6±6.95 years ranging from 15 to 40 years. The different percentage of valvular lesions in RHD were MR (59.06%), MS (46.78%), AR (43.85%) and mixed lesions (38.59%). Conclusion: Rheumatic heart disease is a very common disease in our community and mitral regurgitation is a predominant lesion at presentation Females are usually affected more than males. Keywords: Rheumatic heart disease, Mitral stenosis, Mitral regurgitation, Aortic regurgitation